Psychological Characteristics Of Doctor And Patient Communication - Askarova Nargiza Abdivalievna; Ahmadjanov Ibrahim Ilhomjon ogli (Genius Publishing Group, 2022)
In modern healthcare, the ability of a doctor to combine pharmacological methods and communication skills is becoming increasingly valuable. Respect, trust and empathy are critical to communication between doctor and patient. They reduce dissatisfaction and promote better patient discipline. In addition, these qualities influence the decisions that patients make regarding treatment. The physician must be flexible enough to deal with a wide variety of patients. The article discusses specific approaches to different types of patients.
Keywords: Communication; Physician; Psychoanalysis; Hypochondriac